Village Government Efforts to Improve Public Services (Case Study of Poto Village) - Kariyani, Leni Nurul (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study is to find out how the Village Government's Strategy in Improving the Quality of Public Services at the Poto Village Office.In this study, the author used a qualitative approach, namely to know or describe the reality of the events studied so as to make it easier for the author to obtain objective data in order to know and understand the strategies used in improving the quality of service in the poto village office.The results showed that the Village Government's Strategy in Improving the Quality of Public Service at the Poto Village Office, Moyo Hilir District, is in accordance with the village head's regulation Number 7 concerning the order and implementation of duties and services, regulation Number 8 of 2021 concerning village rules and regulations Number 3 of 2016 concerning the Medium-Term Development Plan (RPJM Desa) for 2021-2026 CHAPTER IV concerning the direction of development policies and strategies in improving quality Service. In an effort to improve the quality of public servants in the poto village office and all village officials provide the best service to provide the facilities needed by the community.Researchers expect the village government in carrying out its duties as a public service in order to maintain professionalism and carry out the rules that have been set in improving the quality of public services and the welfare of the community and with several obstacles in serving the community, it is hoped that the village government can face and find solutions so that they can answer the challenges of the community.